Development of Reading, Questioning, and Answering (RQA)-Based Modules in Biology - Nurvia, Indah Wahyu; Mellisa, Mellisa (Program Studi Pendidikan Biologi FKIP Universitas Pakuan, 2023)
The model of 21st century learning applies creativity, critical thinking, cooperation, problem solving, communication, community and character skills. Learning media is a supporting tool in the teaching and learning process, learning media is designed to attract or stimulate student interest and make it easier for students to understand the material. One solution that can be implemented is to develop a learning module based on Reading, Questioning, and Answering (RQA). Based on this, this research aims to find out how valid and practical the RQA-based module is. This research method is Research and Development model used is ADDIE. The research results show that the RQA-based module learning media is suitable for use. It can be concluded that learning media is used effectively and efficiently in the learning process.